Workspace analysis and motion control strategy of robotic mine anchor drilling truck manipulator based on the WOA-FOPID algorithm - Jun, Zhang; Yiliang, Wang; Liming, Che; Ning, Wang; Yuepin, Bai; Chaofan, Wang (Frontiers in Earth Science, 2022)
The manipulator is the key component of the anchor drilling robot to automatically complete the anchoring operation underground. Due to the complexity of its motion equation and the limitations of its control strategy, the real-time pose and positioning accuracy of the manipulator are inferior, which seriously restricts the safety, efficiency and speed of roadway excavation. In order to improve the positioning accuracy and realize optimal efficiency of the manipulator, this paper designs a manipulator structure with four degrees of freedom. With the help of D-H method and intelligent parameter setting method, this paper carries out the basic theoretical research on the kinematics and fractional order FOPID control algorithm of the manipulator of the mining roof bolter, and formulates a manipulator motion control strategy. At the same time, combined with numerical simulation and field experiment, we explore the robustness and control effect of the hydraulic system of the manipulator under the working conditions of harsh environment and limited space, and reveal that the intelligent optimization algorithm can control the motion state of the manipulator more accurately and stably after the parameters of the fractional order FOPID controller are positively determined. This study effectively solved the dynamic model uncertainty caused by time-varying internal parameters and external loads of the hydraulic servo system, optimized and reconstructed the structure and motion coefficient parameters of the manipulator, and revealed the control mechanism of precise spatial positioning and online trajectory planning of the hydraulic servo system of the manipulator. Compared with the traditional PID control algorithm, this algorithm has faster response speed and better expected track tracking ability. This research lays a theoretical foundation for precise positioning and automatic support of the manipulator, and also provides a reference for the design of similar motion control algorithms.